Crack-inclusion interaction in composite materials with aerospace and offshore engineering applications - Lim, Yu Cong (Nanyang Technological University, 2024)
Composite materials have several mechanical qualities that improve their performance in engineering applications and are widely used in many industries. Inclusions and cracks often occur together and are influenced by one another. The crack that forms and spreads to reach the inclusion material will either stop or continue to propagate when an inclusion with a comparatively different Young's modulus occurs in a plate. The stress intensity factor (SIF), which aids in crack propagation prediction, can be found by measuring the separation between the inclusion and the crack tip. Ansys software is being used for the project to simulate a two- dimensional model that solely addresses plane strain. Because of this assumption, the complexity and equations of the problems have been made simpler, making the solutions more accurate and manageable.